ABA Alleviates Uptake and Accumulation of Zinc in Grapevine (Vitis vinifera L.) by Inducing Expression of ZIP and Detoxification-Related Genes - Song, Changzheng; Yan, Yifan; Rosado, Abel; Zhang, Zhenwen; Castellarin, Simone Diego (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) is a stress phytohormone which can mitigate heavy metal toxicity. Exogenous ABA and ABA mimic 1 (AM1) were applied to study the influence on Zn uptake and accumulation in Vitis vinifera L. cv. ‘Merlot’ seedlings exposed to excess Zn. The seedlings were treated with either normal or excess levels of Zn in combination with ABA and AM1 applications. The excess Zn exposure resulted in decreased lateral root length, decreased photosynthesis, elevated uptake and accumulation of Zn in roots, trunks, and stems, increased content of jasmonic acid in roots and leaves, and induced the expression of Zn transportation and detoxification related genes. Exogenous applications of ABA, but not AM1, alleviated the over-uptake and accumulation of Zn in roots and trunks at 10 days after Zn exposure and induced higher expression of both ZIP genes and detoxification-related genes. These results indicate that exogenous ABA enhances the tolerance of grape seedlings to excess Zn, and that AM1 is not a suitable ABA mimic compound for Zn stress alleviation in grapes.